Global geographical range and population size of the habitat specialist Codonoblepharon forsteri (Dicks.) Goffinet in a changing climate. (2nd January 2022) - Callaghan, Des A.; Aleffi, Michele; Alegro, Antun; Bisang, Irene; Blockeel, Tom L.; Collart, Flavien; Dragićević, Snežana; Draper, Isabel; Erdağ, Adnan; Erzberger, Peter; Garcia, César A.; Garilleti, Ricardo; et al.
ABSTRACT: Introduction: Codonoblepharon forsteri (Dicks.) Goffinet is a rare epiphytic moss characteristically associated with water-filled holes in trees. We reviewed its range and population and assessed effects of climate change. Methods: An inventory of sites from where Codonoblepharon forsteri has been recorded was compiled. Extent of occurrence (EOO) and area of occupancy (AOO) were calculated. Population size was estimated, treating an occupied tree as an 'individual-equivalent' of the moss. Climatic conditions of the species' current distribution were characterised, and an ensemble model of its distribution was generated. The latter was projected onto present and future climatic layers. Key results: Codonoblepharon forsteri has been recorded from 19 countries and 205 sites in Europe, North Africa and Southwest Asia. It has been undergoing an overall decline. Most sites have few occupied trees, and a world population of 1000–10, 000 individual-equivalents is estimated. Model projections suggest that the species will experience a range increase of +0.36–0.65 by 2050 and +0.35–0.68 by 2070, especially in its northwest range, particularly across France and the UK. Range loss is predicted to be between –0.20 and –0.39 in 2050 and –0.21 and –0.65 in 2070, affecting the driest areas of the current range around the Mediterranean, especially in North Africa. Conclusions: Codonoblepharon forsteri has a relatively large EOO but relatively small AOO, probably due to habitat specialism. A major reason for recent declines appears to be widespread abandonment of traditional 'pollarding' of trees. The potential climatic range of the species will shift significantly northwards over the next few decades.